PENGARUH KOMITMEN ORGANISASI DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI BADAN PENDAPATAN DAERAH KABUPATEN DELI SERDANG - Teguh Abdi Syahputra; Tukimin Tukimin (Universitas Dharmawangsa, 2022)
This study aims to determine whether there is an influence between organizational commitment and the quality of human resources on employee performance, using descriptive and quantitative methods. The sample used is as many as 99 respondents, namely employees of the State Civil Apparatus (ASN) of the Regional Revenue Agency of Deli Serdang Regency. The results obtained are organizational commitment and the quality of human resources affect the performance of regional revenue agency employees of Deli Serdang Regency as shown from the results of multiple regression Y = 12.090 + 0.223X1 + 0.482X2 + e. With the results of the partial test (t test) of organizational commitment with a value of tcount = 1.921>1.66 and the results of the partial test (t-test) for the quality of human resources, namely tcount = 4.480>1.66, this indicates that organizational commitment and quality of resources Human resources have a positive effect on the performance of State Civil Apparatus (ASN) employees of the Regional Revenue Agency of Deli Serdang Regency. For the F test results obtained Fcount>Ftable (62,701>3,091). The value of the coefficient of determination (R2) is 0.566, which means that organizational commitment and the quality of human resources are able to improve the performance of employees of the regional revenue agency of Deli Serdang Regency, by 56.6% and the remaining 43.4% is explained by other variables outside the study.